Stability Analysis of Tuberculosis SITS Model - Wahyudin Nur; Magfirah Magfirah; Darmawati Darmawati; Ahmad Ansar (Program Studi Matematika Universitas Sulawesi Barat, 2020)
Tuberculosis (TB) is an infectious disease caused by mycobacterium tuberculosis. The purpose of this study is to investigate the dynamics of TB spread by using mathematical model. We develop SITS model which expressed as system of differential equations. The system has two equilibrium points, namely disease-free equilibrium point and endemic equilibrium point. The stability condition of the equilibrium points is proved. We perform several numerical simulations to support our theoretical results.